Does fetal sex affect placental delivery times? A prospective observational study. (17th January 2020) - Tosun, Gökhan; İnan, Abdurrahman Hamdi; Kanmaz, Ahkam Göksel; Biler, Alper; İleri, Alper; Beyan, Emrah; Ertas, Ibrahim Egemen
Abstract: Objective: The aim of this study was to determine the potential effect of fetal sex on placental delivery times. Study design: This was a prospective observational study of term, singleton, and primiparous pregnant women who underwent vaginal delivery and subsequently delivered a phenotypically normal live infant. Women with labor or pregnancy complications and comorbid diseases were excluded. Women with factors who could lengthen the placental delivery time were also excluded. The cohort was divided into two groups according to fetal sex. A total of 299 vaginal deliveries were included, and placental delivery times were analyzed in both groups. Results: There were 3938 vaginal deliveries during the study period. Of these, 150 male-bearing pregnant women and 149 female-bearing pregnant women who met the inclusion criteria were included in the analysis. The mean placental delivery time was significantly longer in the male-bearing group than the female-bearing group (12.20 versus 8.21 min, p  = .01). Birth weight was significantly greater in the male-bearing group than the female-bearing group (3194 versus 3059 g, p  = .004). There was no significant between-group difference in maternal age, gestational age, and preconception body mass index (BMI). Conclusion: Fetal sex had a significant effect on the placental delivery time in the present study. Fetal sex should be considered in future clinical trials of placental delivery times.